2007
DOI: 10.4161/cc.6.2.3760
|View full text |Cite
|
Sign up to set email alerts
|

GPR56 and TG2: Possible Roles in Suppression of Tumor Growth by the Microenvironment

Abstract: Metastasis is a complex process that involves multiple levels of cell-cell interaction. Among these interactions, tumor-stroma interactions are being actively investigated. Metastatic cells are hypothesized to show gene expression changes that contribute to their survival and growth at the distant site. Such changes could contribute either to enhancement of growth or to evasion of growth inhibition by the normal tissue environment thus allowing growth as metastases. Our recent report that tumors from highly me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 78 publications
1
34
0
Order By: Relevance
“…Furthermore, it enables us to confirm unambiguously that human TG2 is not a cellular ligand for GPR56. This result not only points to the presence of a novel protein ligand for GPR56 but also challenges the biological relevance of the interaction between human GPR56 and mouse TG2 (20,27).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, it enables us to confirm unambiguously that human TG2 is not a cellular ligand for GPR56. This result not only points to the presence of a novel protein ligand for GPR56 but also challenges the biological relevance of the interaction between human GPR56 and mouse TG2 (20,27).…”
Section: Discussionmentioning
confidence: 91%
“…Collagen, type III, a-1 (gene symbol, COL3A1) has been proposed as the ligand of GPR56 (Luo et al, 2011), signaling by activating RhoA through coupling to G 12/13 . Transglutaminase 2, a major crosslinking enzyme in the extracellular matrix, has also been proposed as a ligand of GPR56 (Xu and Hynes, 2007).…”
Section: B Class Bmentioning
confidence: 99%
“…Therefore, research of this family has not progressed well. It has been reported that transglutaminase 2 (TG2), 6) CD81, 7) and collagen III 8) are the interactors of GPR56. Collagen III has been shown to inhibit the cell migration of neural progenitor cells.…”
mentioning
confidence: 99%